Low dose of uranium induces multigenerational epigenetic effects in rat kidney. (2nd November 2018) - Grison, Stéphane; Elmhiri, Ghada; Gloaguen, Céline; Elie, Christelle; Kereselidze, Dimitri; Tack, Karine; Lestaevel, Philippe; Legendre, Audrey; Manens, Line; Benadjaoud, Mohamed Amine; Lobaccaro, Jean-Marc; Souidi, Maâmar
Abstract: Purpose: A protocol of chronic exposure to low dose of uranium was established in order to distinguish the sexual differences and the developmental process that are critical windows for epigenetic effects over generations. Methods: Both male and female rats were contaminated through their drinking water with a non-toxic solution of uranyl nitrate for 9 months. The exposed generation (F0) and the following two generations (F1 and F2) were examined. Clinical monitoring, global DNA methylation profile and DNA methyltransferases (DNMTs) gene expression were analyzed in kidneys. Results: While the body weight of F1 males increased, a small decrease in kidney and body weight was observed in F2 males. In addition, global DNA hypermethylation profile in kidney cells was observed in F1 and F2 males. qPCR results reveal a significant increase of methyltransferase genes expression ( DNMT1 and DNMT3a ) for F2 females. Conclusions: In the field of public health policy and to raise attention to generational effects for the risk assessment of the environmental exposures, low doses of uranium do not imply clinical effects on adult exposed rats. However, our results confirm the importance of the developmental windows' sensitivity in addition to the sexual dimorphisms of the offspring.